Some Considerations Affecting the Long-Run Trend of the Building Industry - Clark, W. C. (The Review of Economics and Statistics, 1926)
IN the case of most statistical series the abnormal features of the war and early postwar years made extraordinarily difficult the calculation of which could be projected into the future for forecasting purposes. In no other case, however, has this difficulty been so great as in the statistics of the building industry. Today, 7 years after the close of the war, we are still not only in the dark as to what the trend of the industry is likely to be during the next few years, but also equally confused, because lacking adequate standards of judgment, as to the significance of the intense activity of the recent past. In the present paper brief reference will be made to certain recent studies which have calculated or assumed building normal for the purpose of estimating the extent to which the accumulated building shortage of the war and post-war years has been made up, and consideration will be given to the factors which will affect the building normal of the future. Most of the earlier attempts' to calculate building followed the course of endeavoring, by the method of least squares, to fit straight line to the data representing the annual value of building permits issued in large number of cities over long period of time. Because of the difficulties involved in determining normal period of adequate length and of making allowance for the effect of changes brought about by the war, none of these studies have produced long-term trend lines which have been received with any large measure of confidence, especially for forecasting purposes. A second group of investigators have sought the elusive of the building industry by plotting building permits against population growth instead of solely against time. For instance, Mr. H. B. Byer of the United States Bureau of Labor Statistics has recently published the results of an investigation in which he assumed that the line of population increase is the normal line of increase. 2 The validity of this assumption is to be considered later. At the present time it is sufficient to note that his investigation resulting in the conclusion that at the end of I924 had not only made up for the war shortage but was actually about four-tenths ahead of current needs is subject to the obvious criticism that the author used as the basis of his calculations the value of permits issued in single, and by no means typical year, namely, I9I4. The same general assumption that building varies directly and proportionately with population is the starting point of another investigation into the building shortage by the research staff of the National Bank of Commerce.3 Starting with the more normal year, I9I3, as the base, this study developed a trend of building requirements or a line of normal growth of construction which was based simply on the annual population of the 66 urban centers selected. Incidentally, the conclusion reached was that at the end of I924, building shortage of over 3 billion dollars still remained. Of this same general type was the well-known study of the building shortage made by Col. L. P. Ayres, in I922.4 His was found by fitting line, by the method of least squares, to the data representing the annual value of building permits per capita of population for 50 cities for the period I900 to I9I6. It therefore assumed that building operations varied directly with population. The period chosen, moreover, was subject to the criticism that it began with year of abnormally low activity and ended with one of fairly high activity. To the present writer the underlying assumption of this second type of investigation does